(untitled) (Damascus University Journal for the basic sciences, 2022)
The aim of this research was studying the effect of plant growth regulators (Auxins and Cytokinins) on plant regeneration and micro corm formation in Crocus sativus L.var. Coupe. We used MS medium (Murashige and Skooge) with Casinehydrolite (500 mg.l-1) and proline (600 mg.l-1) in addition to 6-BAP (0, 0.5, 1, 1.5, 2, 2.5 and 3) mg.l-1 and 2,4-D (0 and 0.175) mg.l-1 to determine the best plant growth mixture for plant regeneration and number of shoots whereas we use different medium (MS0: without plant growth, MS1: 1 mg.l-1 IBA, MS2: 2 mg.l-1 IBA, MS3: 1 mg.l-1 BAP+ 1 mg.l-1 IBA, MS4: 1 mg.l-1 BAP+ 0.5 mg.l-1 NAA, MS5: 0.5 mg.l-1 BAP,MS6: 2 mg.l-1 BAP and MS7: 4 mg.l-1 BAP ) to determine the best medium for corms formation. The results revealed that the highest average ratios of shoot regeneration were (60.38, 55.19 and 53.7 %) in the concentration (1 mg.l-1 6-BAP, 0.5 mg.l-1 6-BAP and 1 6-BAP + 0.175 mg.l-1 2,4-D ) respectively. The significantly highest average ratios of shoot numbers at the concentrations (1 mg.l-1 6-BAP, 0.5 mg.l-1 6-BAP + 0.175 mg.l-1 2,4-D and 0.5 mg.l-1 6-BAP ) were (7.1, 6.94 and 6.7) shoots/plant respectively.